2016
DOI: 10.14245/kjs.2016.13.3.167
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Spinal Epidural Hematoma Coexisting Guillan-Barré Syndrome in a Child: A Case Report

Abstract: Spontaneous spinal epidural hematoma (SSEH) has been reported as a rare cause of spinal cord compression, especially in children. Clinical features are usually nonspecific, although cervicothoracic location of hematoma could be presented with progressive paraplegia. Guillian-Barré syndrome (GBS) is clinically defined as an acute peripheral neuropathy causing progressive limb weakness. Because SSEH and GBS have very similar signs and symptoms, SSEH could be misdiagnosed as GBS. Nevertheless, they can be present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The pediatric case (case 5) was initially misdiagnosed and treated as Guillain-Barré syndrome (GBS). SSEH can develop in infants and children as well as adults 16 , and there are a few reports wherein SSEH in pediatric patients was misdiagnosed as GBS 17,18 . The authors of these cases indicated the similarity of initial symptoms in SCEH and GBS of progressive palsy in the limbs.…”
Section: Discussionmentioning
confidence: 99%
“…The pediatric case (case 5) was initially misdiagnosed and treated as Guillain-Barré syndrome (GBS). SSEH can develop in infants and children as well as adults 16 , and there are a few reports wherein SSEH in pediatric patients was misdiagnosed as GBS 17,18 . The authors of these cases indicated the similarity of initial symptoms in SCEH and GBS of progressive palsy in the limbs.…”
Section: Discussionmentioning
confidence: 99%
“…Laminectomies were the surgical interventions of choice, and most tried conservative therapy before surgery. Of the surgical cases, six (50%) were neurologically intact after surgery [27][28][29][30][31][32], four (33%) had a neurological sequela [33][34][35][36], and two (17%) died [37,38]. The conservative approach was chosen for 21 patients, from which 19 (90%) were neurologically intact after intervention with factor replacement [5,8,23,30,[39][40][41][42][43][44][45][46][47][48][49][50][51][52], two (10%) had some kind of sequela, and none died [10,53].…”
Section: Discussionmentioning
confidence: 99%
“…GBS is an inflammatory demyelinating polyradiculopathy, characterized by acute areflexic paralysis and demyelinating changes in the peripheral nervous system. The majority of cases are preceded by upper respiratory infection or diarrhea, with the most frequently identified infectious agent being Campylobacter jejuni, followed by cytomegalovirus 6 , 8 , 10) . The main feature of GBS is progressive bilateral and relatively symmetric weakness of the limbs, with the weakness progressing over a period of 12 hours to 28 days before a plateau is reached 15) .…”
Section: Discussionmentioning
confidence: 99%